THE COMPUTATION OF THE GEOID MODEL IN THE STATE OF SÃO PAULO USING TWO METHODOLOGIES AND GOCE MODELS - GUIMARÃES, GABRIEL DO NASCIMENTO; BLITZKOW, DENIZAR; BLITZKOW, DENIZAR; BARZAGHI, RICCARDO; BARZAGHI, RICCARDO; DE MATOS, ANA CRISTINA OLIVEIRA CANCORO; DE MATOS, ANA CRISTINA OLIVEIRA CANCORO (Boletim de Ciências Geodésicas, 2014)
The purpose of this manuscript is to compute and to evaluate the geoid model in the State of São Paulo from two methodologies (Stokes’ integral through the Fast Fourier Transform - FFT and Least Squares Collocation – LSC). Another objective of this study is to verify the potentiality of GOCE-based. A special attention is given to GOCE mission. The theory related to Stokes’ integral and Least Squares Collocation is also discussed in this work. The spectral decomposition was employed in the geoid models computation and the long wavelength component was represented by EGM2008 up to degree and order 150 and 360 and GOCE-based models up to 150. The models were compared in terms of geoid height residual and absolute and relative comparisons from GPS/leveling and the results show consistency between them. In addition, a comparison in the mountain regions was carried out to verify the methodologies behavior in this area; the results showed that LSC is less consistent than FFT.